Age-Dependent Changes in Transcription Factor FOXO Targeting in Female Drosophila - Birnbaum, Allison; Wu, Xiaofen; Tatar, Marc; Liu, Nan; Bai, Hua (Frontiers in Genetics, 2019)
FOXO transcription factors have long been associated with longevity control and tissue homeostasis. Although the transcriptional regulation of FOXO have been previously characterized (especially in long-lived insulin mutants and under stress conditions), how normal aging impacts the transcriptional activity of FOXO is poorly understood. Here, we conducted a chromatin immunoprecipitation sequencing (ChIP-Seq) analysis in both young (2-week-old) and aged (5-week-old) wild-type female fruit flies, Drosophila melanogaster, to evaluate the dynamics of FOXO gene targeting during aging. Intriguingly, the number of FOXO-bound genes dramatically decreases with age (from 2617 to 224). Consistent to the reduction of FOXO binding activity, many genes targeted by FOXO in young flies are transcriptionally altered with age, either up-regulated (FOXO-repressing genes) or down-regulated (FOXO-activating genes) in adult head tissue. In addition, we show that many FOXO-bound genes in wild-type flies are unique from those in insulin receptor substrate chico mutants. Distinct from chico mutants, FOXO targets specific cellular processes (e.g., actin cytoskeleton) and signaling pathways (e.g., Hippo, MAPK) in young wild-type female flies. FOXO targeting on these pathways decreases with age. Interestingly, FOXO targets in aged flies are enriched in cellular processes like chromatin organization and nucleosome assembly. Furthermore, FOXO binding to core histone genes is well maintained at aged flies. Together, our findings provide new insights into dynamic FOXO targeting under normal aging and highlight the diverse and understudied regulatory mechanisms for FOXO transcriptional activity.